FIRST RESULTS OF THE NEW HUNGARIAN HYPERTENSION REGISTRY: SEASONAL CHANGES OF BLOOD PRESSURE VALUES. (April 2021) - Páll, Dénes; Nemcsik, János; Habony, Norbert; Farsang, Csaba; Ábrahám, György; Simon, Attila; Benczúr, Béla; Járai, Zoltán
Abstract : Objective: It is well known that blood pressure (BP) changes continuously and there is a seasonal change of BP. Our aim was to examine how these changes are present among the Hungarian population. Design and method: Omron M3 IT devices were placed to physicians between October 2018 and November 2019. All of the measured BP values were transmitted online to an evaluating center using the Medistance system of Omron. 1.691 general practitioners and 235 internists have been involved in the study. Based on this database, we analyzed the seasonal changes of BP in our population. Results: At this moment we have more than a million (1.008.398) BP data in our new Hungarian Hypertension Registry. Separating these BP data by month, we found the highest systolic BP average in winter (in December 141.84 mmHg, January 142.00 mmHg, February 141.47 mmHg). On the other hand, the lowest systolic BP data were measured in summer (in June 136.74 mmHg, July 137.10 mmHg, August 135.86 mmHg). We observed the same trend comparing diastolic BP. The highest average values were in January (85.48 mmHg), December (85.02 mmHg), February (84.93 mmHg) and the lowest were measured in August (82.13 mmHg), June (82.82 mmHg), July (83.11 mmHg). During spring and autumn, the BP values were between our winter and summer data. The mean difference between the average of the highest and lowest month (January vs August) is 6.34 mmHg for systolic, and 3.35 mmHg for diastolic BP. In summer (June, July, August) the ratio of the well-controlled hypertensives was 51.37%, 51.05% and 53.51%, respectively, while it was only 42.1%, 41.76% and 42.53% in December, January and February. We observed grade III. hypertension in 5.09%, 6.11% and 5.75% in summer, while it was much higher in winter (7.44%, 7.79%, 7.3%). Conclusions: There is an important difference in the average values of our winter and summer BP data, and the ratio of the well-controlled as well as the severe hypertensives. Based on these data there can be need for seasonal change in the quantity of their antihypertensive drugs to reach the optimal BP values.